2005
DOI: 10.4049/jimmunol.175.11.7602
|View full text |Cite
|
Sign up to set email alerts
|

Impaired FcεRI-Dependent Gene Expression and Defective Eicosanoid and Cytokine Production as a Consequence of Fyn Deficiency in Mast Cells

Abstract: Fyn kinase is a key contributor in coupling FcεRI to mast cell degranulation. A limited macroarray analysis of FcεRI-induced gene expression suggested potential defects in lipid metabolism, eicosanoid and glutathione metabolism, and cytokine production. Biochemical analysis of these responses revealed that Fyn-deficient mast cells failed to secrete the inflammatory eicosanoid products leukotrienes B4 and C4, the cytokines IL-6 and TNF, and chemokines CCL2 (MCP-1) and CCL4 (MIP-1β). FcεRI-induced generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 68 publications
(75 reference statements)
8
108
1
Order By: Relevance
“…Our findings are in agreement with several previous studies that demonstrated the involvement of PI3K/p38 activated pathway, Fc RI-induced IL-4 production in the mast cell (23,35). It is known that PI3K regulates the activation of Rac, which, in turn, activates p21-activated kinase resulting in the induction of p38 MAPK and JNK (36).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are in agreement with several previous studies that demonstrated the involvement of PI3K/p38 activated pathway, Fc RI-induced IL-4 production in the mast cell (23,35). It is known that PI3K regulates the activation of Rac, which, in turn, activates p21-activated kinase resulting in the induction of p38 MAPK and JNK (36).…”
Section: Discussionsupporting
confidence: 93%
“…It is known that PI3K regulates the activation of Rac, which, in turn, activates p21-activated kinase resulting in the induction of p38 MAPK and JNK (36). Moreover, the Fyn kinase is known to be required for PI3K activation, and Fyn deficiency results in the reduction of both p38 MAPK and JNK activation but not that of ERK (23). Additionally, the importance of MAPKs for Th2 cytokine production has been reported (37).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations